New records of Pachycrepoideus vindemmiae (Hymenoptera: Pteromalidae) associated with Drosophila suzukii (Diptera: Drosophilidae) in cherry and berry crops from Argentina - Funes, Claudia Fernanda; Garrido, Silvina Alejandra; Aquino, Daniel Alejandro; Escobar, Lorena Ines; Gomez Segade, Carolina Belen; Cichon, Liliana; Ovruski Alderete, Sergio Marcelo; Kirschbaum, Daniel Santiago (Sociedad Entomológica Argentina, 2021)
New records of the ectoparasitoid Pachycrepoideus vindemmiae (Rondani) (Hymenoptera: Pteromalidae) associated with Drosophila suzukii Matsumura (Diptera: Drosophilidae) in the provinces of Tucumán, Río Negro and Neuquén are cited. Detections occurred in blueberry, raspberry and cherry crops. The records from Río Negro and Neuquén constitute the southernmost report of the species. Diagnosis and prevalence of the parasitoid are briefly discussed.